(untitled) (International Journal of Engineering and Computer Science, 2018)
— MOSFETs have been the most popular devices for past five to six decades because of its excellent scalability. But during past few years semiconductor industry is facing various challenges related to scaling. These challenges are related to several fundamental and practical of underlying physics of device such as leakage currents, mobility, reliability, sub threshold swing and in turn degrading the device performance. MOSFET is most uses in inverter, power amplifier and switching devices for electronics. As IMOS will be a good alternative for small scale devices due to its good electrical performances. Its low sub threshold swing property will be very beneficial for high switching devices but this device faces a very critical issue of high operating voltage to operate in ON state and as device is scaled down chances of band to band tunneling is high which increase the leakage current in the device. This paper focus on the problem to reduce the required supply voltage and thresh-old voltage by optimizing its various physical parameter like its Gate length, Intrinsic length and Oxide thickness etc. Apart from this we propose some novel structure of device called Ultrathin IMOS and Silicide based UTIMOS based on the optimization result. These devices have better performance as compare to conventional LIMOS structure.In this paper, a detailed analysis has been done for Lateral impact ionization MOS.